Effect of combined farnesoid X receptor agonist and angiotensin II type 1 receptor blocker on hepatic fibrosis. Issue 9 (19th September 2017) - Namisaki, Tadashi; Moriya, Kei; Kitade, Mitsuteru; Takeda, Kosuke; Kaji, Kosuke; Okura, Yasushi; Shimozato, Naotaka; Sato, Shinya; Nishimura, Norihisa; Seki, Kenichiro; Kawaratani, Hideto; Takaya, Hiroaki; et al.
Abstract : The farnesoid X receptor (FXR) agonist, a bile acid‐activated nuclear receptor, has been shown to improve the histologic features of nonalcoholic steatohepatitis (NASH); however, a satisfactory effect on hepatic fibrosis has not been achieved. We aimed to investigate the combined effect of FXR agonist and angiotensin II type 1 receptor blocker on hepatic fibrogenesis in rat models of NASH. For 8 weeks, two rat models of NASH were developed. Otsuka Long‐Evans Tokushima Fatty (OLETF) rats were administered intraperitoneal injections of 1 mL/kg pig serum (PS) twice a week, whereas Fischer‐344 rats were fed a choline‐deficient, L‐amino acid‐defined diet (CDAA). The in vitro and in vivo effects of an FXR agonist (INT747) and an angiotensin II type 1 receptor blocker (losartan) on hepatic fibrogenesis were evaluated. In PS‐administered OLETF rats, INT747 and losartan had potent inhibitory effects on hepatic fibrogenesis with suppression of hepatic stellate cell (HSC) activation and expression of transforming growth factor β1 and toll‐like receptor 4. INT747 decreased intestinal permeability by ameliorating zonula occuludens‐1 disruption, whereas losartan directly suppressed activated‐HSC (Ac‐HSC) regulation. The in vitro inhibitory effects of INT747 and losartan on messenger RNA expressions of transforming growth factor β1, toll‐like receptor 4, and myeloid differentiation factor 88 and phosphorylation of nuclear factor‐κB and mothers against decapentaplegic homolog 3 in Ac‐HSC were almost in parallel. Losartan directly inhibited the regulation of Ac‐HSC. Likewise, INT747 in combination with losartan was beneficial on hepatic fibrogenesis in rats fed with CDAA diet. The therapeutic effects of these agents were almost comparable between PS‐administered OLETF and CDAA‐treated rats. Conclusion : INT747 and losartan synergistically suppressed hepatic fibrogenesis by reversing gut barrier dysfunction and inhibiting Ac‐HSC proliferation. Combined therapy may represent a promising novel approach for NASH. ( Hepatology Communications 2017;1:928–945)